PERANCANGAN KAWASAN WISATA KESEHATAN DAN KEBUGARAN DI TEPIAN DANAU SARI EMBUN BATI-BATI KABUPATEN TANAH LAUT - Aditama, Hefri; Nurfansyah, Nurfansyah (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
ABSTRACT Improving health and body fitness during the COVID-19 pandemic has become a concern for many people to survive. Starting at the end of 2019, the COVID-19 pandemic hit the whole world, including Indonesia. Many prevention methods have been carried out to avoid exposure to this virus, such as using masks, keeping a distance from other people, maintaining cleanliness, and doing activities at home. However, now the pandemic period has passed and has been replaced by a post-pandemic policy, namely the new normal so that we can return to doing activities outside the home, especially recreation. Health and wellness tourism is a resort object based on education, recreation, exercise and sports for the purpose of improving health and body fitness. The background is post-pandemic and applies the concept of public health to avoid exposure to COVID-19. As well as with a sustainable architecture design strategy through environmentally friendly designs.